Strategy Management Semi-Islamic Boarding Schools - Afiful Ikhwan; Ariska Nupita Yuniana (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
This paper aims to examine the madrasa development strategy in improving the quality of its Human Resources, which is not focused on just one, but as a whole, starting from the leaders, educators, education staff (staff), stakeholders, and guardians of the students. Correlate-apply between the family and school educational environment with the concept of semi-Islamic boarding school management. This study uses a descriptive qualitative method with a case study design, data acquisition using interviews and observation methods, and data analysis using triangulation with the research locus at Madrasah Ibtidaiyah Pesantren Anak Soleh (MI PAS) Baitul Qur'an Gontor, Ponorogo, East Java, Indonesia. The results of the study: (1) The implementation of strategies to improve the quality of human resources is very detailed, such as (a) upgrading teachers every semester, which aims to maintain the sincerity of ruhul-mudarris with the concept of the five strengths of K.H Abdullah Syukri, (b) workshops aimed at improving pedagogical and professional competencies, (c) comparative studies aimed at obtaining inspiration and public relations networks, and (d) training in al-Qur'an certification as an emphasis on the vision of the locus and (2) indicators and implications of integration using (a) musabaqah (competition) with the concept of competing with each other. in goodness (improvement of achievement), (b) parenting skills (childcare patterns) for wali santi, (c) family gathering for friendship events, (d) evaluation and scheduled work meetings. All are carried out to achieve good communication, coordination and collaboration. To deliver the institution in achieving the educational vision, mission and goals.